given is the following series

$$\sum_{n=1}^\infty \frac{2n+1}{n^2(n+1)^2}$$

And I need to find its value.

How can I start finding it?

Thanks for all

does the Telescop-Summing work here as well?:

$\sum_{n=1}^\infty \frac{1}{4n^2-1} $ now: $\frac{1}{4n^2-1} = \frac{1}{2} * \frac{(2n+1)-(2n-1)}{(2n+1)(2n-1)} = \frac{1}{2} * ( \frac{1}{2n-1} - \frac{1}{2n+1})$

Now I have to "add the sum": $\sum_{n=1}^\infty \frac{1}{4n^2-1} = \frac{1}{2}* [ \sum_{n=1}^\infty \frac{1}{2n-1} - \sum_{n=1}^\infty \frac{1}{2n+1}] = \frac{1}{2} - \frac{1}{4n+2} $ And than for $n \to \infty$ it is $\frac{1}{2}$ ??


HINT: $$\frac{2n+1}{n^2(n+1)^2}=\frac{(n+1)^2-n^2}{n^2(n+1)^2}=\frac1{n^2}-\frac1{(n+1)^2}$$

Can you recognize Telescoping Sum?

  • $\begingroup$ Hi, that's a huge hint, thank you very much! :) If I am right, than using the 'Telescoping Sum' in the end I get: $1 - \frac{1}{(n+1)^2}$ and now I look at $ n \to \infty $ and I get: The Value is 1. $\endgroup$ – Vazrael May 21 '13 at 13:47
  • $\begingroup$ @KevinLiebing, welcome. You are right. $\endgroup$ – lab bhattacharjee May 21 '13 at 14:51

split it up the numerator to 2n + 2 - 1 then factor to 2(n+1) -1. By spliting the fraction you can cancel terms. This should allow you to see this is a finite result.

  • $\begingroup$ Are you suggesting that we go $\frac{2n+1}{n^2(n+1)^2}=\frac{2(n+1)-1}{n^2(n+1)^2}=\frac{2-1}{n^2(n+1)}=\frac{1}{n^2(n+1)}$?...! $\endgroup$ – user1729 May 21 '13 at 10:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.